Différences dans la conceptualisation entre le français et le polonais selon l’approche orientée-objets - Perz, Magdalena (Neophilologica, 2013)
It is well known that languages differ in how they describe the same piece of reality. In this paper, the author examine that the categorization of some events does not proceed in identical way in French and in Polish. On the basis of two nouns of French language analysed as an example, according to the object-oriented method, the author shows that in some cases one item could have few equivalents in other language. The lexicographical description was illustrated with the results deriving from two exemplary nouns (storm, frost). The selection of linguistic equivalents depends on the context of units. It causes great problems for the translator above all for the automatic translation. To chose the proper equivalent, the translator has to analyse a number of uses of unit and understand the concept expressed by the expression.